2020
DOI: 10.1007/s10856-020-06456-9
|View full text |Cite
|
Sign up to set email alerts
|

BIO-NAIL: a bacterial cellulose dressing as a new alternative to preserve the nail bed after avulsion

Abstract: Avulsion of the nail plate is the most accomplished surgical procedure among the nail apparatus surgeries. Since it is not possible to use the removed nail to cover the nail bed, some materials have been suggested, however, they are generally not available for use and often at a high cost. To evaluate the use of Bacterial Cellulose (BC) dressing as a biological nail (Bio-Nail) after partial or total avulsion of the nail plate. Twenty-six candidates for nail avulsion, were randomized into two groups: Control, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Clinically, there was a reduction in exsudativas CVUs with loss of subcutaneous tissue, this decrease is directly associated with superficialization and epithelization of the wounds, a result similar to studies with the theme [26,51].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Clinically, there was a reduction in exsudativas CVUs with loss of subcutaneous tissue, this decrease is directly associated with superficialization and epithelization of the wounds, a result similar to studies with the theme [26,51].…”
Section: Discussionsupporting
confidence: 72%
“…The success achieved by the present study may be associated with a longer treatment time and the association of BC gel with the multiperforated film. In preclinical studies, BC gel has demonstrated the ability of vascular neoformation, which might promote an increase of granulation tissues [21,22,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to proteolytic enzymes, gram-negative microflora causes faster wound cleansing, preparing for further treatment with a free skin graft (Czaja et al, 2004). According to clinical data, due to their flexibility, bacterial cellulose dressings are particularly recommended for the treatment of burn wounds in anatomically complex places (ears, face, joint area, hands, feet, genitals) (Oliveira et al, 2020). It has also been shown that combining the dressing with antiseptics, such as silver nitrate, hydroxyquinoline sulphate or boric acid, has a positive effect on reducing burn wound infection (Czaja et al, 2004).…”
Section: Examples Of Bc Dressings In Clinical Applications and In Viv...mentioning
confidence: 99%
“…Figura 1-Membrana de celulose bacteriana associada a esponja Fonte: Foto obtida do estudo de Oliveira et al, (2020. Research, Society and Development, v. 10, n. 16, e50101622773, 2021(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i16.22773 Silveira et al (2016, Magalhães et al (2020) e Oliveira et al (2020) destacaram-se ao criar inovações com a CB para induzir o remodelamento tecidual ao testa-la em área de autoenxerto, utiliza-la como unha (Bio-nail) em pacientes pós avulsão ungueal e no tratamento de tímpano perfurado. Nesses estudos foram avaliados parâmetros semelhantes como tempo de epitelização, intensidade da dor e adesão.…”
unclassified